2021
DOI: 10.3389/fneur.2021.774657
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Consequence Analysis of Advanced Imaging in Acute Ischemic Stroke Care

Abstract: Introduction: The purpose of this study was to illustrate the potential costs and health consequences of implementing advanced CT angiography and perfusion (CTAP) as the initial imaging in patients presenting with acute ischemic stroke (AIS) symptoms at a comprehensive stroke center (CSC).Methods: A decision-simulation model based on the American Heart Association's recommendations for AIS care pathways was developed to assess imaging strategies for a 5-year period from the institutional perspective. The follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…Similar to previous research, the use of CTP was found cost-effective (8,9). However, this study provides a more detailed description of factors causing changes in costs and health effects.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Similar to previous research, the use of CTP was found cost-effective (8,9). However, this study provides a more detailed description of factors causing changes in costs and health effects.…”
Section: Discussionsupporting
confidence: 85%
“…The incremental cost-effectiveness ratio plots per occlusion location and for all occlusion locations together are visualized in Similar to previous research, the use of CTP was found cost-effective (8,9). However, this study provides a more detailed description of factors causing changes in costs and health effects.…”
Section: Probabilistic Sensitivity Analysissupporting
confidence: 61%
See 3 more Smart Citations